Blanket guarantee and restructuring decisions for multinational banks in a bargaining model - Juha-Pekka Niinimäki; Ville Mälkönen (Bank of Finland, 2009)
This paper examines blanket guarantee and restructuring decisions in respect of a multinational bank (MNB) using Nash bargaining, when the threat of a panic motivates countries to take decisions quickly. The failure of the bank would cause unevenly distributed externalities between the countries concerned, which influences restructuring incentives. In equilibrium, the bank is either liquidated or one or both of the countries recapitalizes it. The partition of the recapitalisation costs is sensitive to the country-specific benefits and costs from recapitalisation, panics and liquidation. The home regulator benefits from the privilege of being the only entity that can legally liquidate the MNB. Rational expectations regarding the bargaining result affect the incentives to declare a blanket guarantee.
URN:NBN:fi:bof-20140807163
Keywords: 330